Evaluation of the oxidative status of periparturient mares supplemented with high amount of α-tocopherol. Issue 1 (2nd January 2019) - Martuzzi, Francesca; Bresciani, Carla; Simoni, Marica; Basini, Giuseppina; Quarantelli, Afro; Righi, Federico
Abstract: Aim of the study was to investigate the oxidative status during peripartum period in mares fed high amount of dietary α-tocopherol. α-Tocopherol, ferric reducing ability of plasma (FRAP) and reactive oxygen metabolites (d-ROMs) levels were measured in blood samples from 17 Thoroughbred mares at three intervals: (1) 20 days before the expected foaling date; (2) 12 h following parturition; (3) 7 days post-partum. The levels of α-tocopherol, d-ROMs and FRAP were retrospectively analysed in relation to the number of insemination services (Ins) after foaling performed per conception. The parameters α-tocopherol and d-ROMs evidenced minimal fluctuations during peripartum period while FRAP levels showed a linear decrease. The α-tocopherol did not show significant variations and was numerically higher in mares >10 years old while FRAP levels were significantly higher in older mares in the post-partum. Mares receiving three natural insemination services showed higher levels of FRAP in the pre-partum period ( p = .009) and lower values of α-tocopherol ( p = .015) in the postpartum compared to mares receiving one service. No d-ROMs level differences appeared among service classes. Oxidative stress is not present in periparturient mares fed 2.750 IU of supplementary α-tocopherol. Differences in redox metabolism are detectable between young and old mares. Plasma antioxidant potential is higher in older mares particularly in the post-partum period. Highlights: Oxidative stress is not present in periparturient mares fed 2.750 IU of supplementary α-tocopherol. Antioxidant potential of plasma is higher in mares older than 10 years compared to younger mares. The increased plasma antioxidant potential seems related to an increase in services per conception.